2019
DOI: 10.1111/1744-9987.12823
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Renal Failure as a Possible Risk Factor for Allergic Reaction in Therapeutic Plasma Exchange Using Fresh Frozen Plasma

Abstract: The incidence of allergic reactions in patients with chronic renal failure during plasma exchange using fresh frozen plasma is not well known. We retrospectively reviewed 62 patients who underwent plasma exchange between January 2013 and May 2018. The most common indication for plasma exchange was desensitization/preconditioning for kidney transplant (61.3%, 38/62). The incidence of allergic reactions was significantly higher in patients with chronic renal failure than patients without (57.1% vs. 25.0%, P = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Several studies have reported the frequency and predictors of allergic reactions in PEx therapy using FFP as a replacement fluid (10)(11)(12). In addition, predictive factors for allergy onset have included a young age, diseases other than liver failure (10), chronic kidney disease (11), hyperbilirubinemia (12), and hematocrit <28.5% (13). However, these reports also differ with regard to the primary disease and diagnosis of allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the frequency and predictors of allergic reactions in PEx therapy using FFP as a replacement fluid (10)(11)(12). In addition, predictive factors for allergy onset have included a young age, diseases other than liver failure (10), chronic kidney disease (11), hyperbilirubinemia (12), and hematocrit <28.5% (13). However, these reports also differ with regard to the primary disease and diagnosis of allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The illness has the potential to gradually progress into uremia, posing a significant threat to the health and well-being of individuals. [ 1 ] The progressive development of CRF is primarily driven by renal fibrosis, which is characterized by the loss of nephrons, excessive synthesis of extracellular matrix (ECM), proliferation of many fibroblasts and myofibroblasts, glomerulosclerosis, and interstitial fibrosis. [ 2 ] Transforming growth factor beta 1 (TGF-β1) is a significant fibrogenic factor that has many effects on mesangial cells.…”
Section: Introductionmentioning
confidence: 99%